Orthogonality and parallelism of operators on various Banach Spaces - Bottazzi, Tamara Paula (2019)
Fil: Bottazzi, Tamara P. Instituto Argentino de Matemática “Alberto P. Calderón”. Buenos Aires, Argentina.